GENETIC METHODS FOR DETECTION OF ANTIBIOTIC RESISTANCE: FOCUS ON EXTENDED-SPECTRUM β-LACTAMASES - Chroma, Magdalena; Kolar, Milan (Biomedical papers, 2010)
Background: In 1928, the first antibiotic, penicillin, was discovered. That was the beginning of a great era in the development and prescription of antibiotics. However, the introduction of these antimicrobial agents into clinical practice was accompanied by the problem of antibiotic resistance. Currently, bacterial resistance to antibiotics poses a major problem in both hospital and community settings throughout the world.Methods and results: This review provides examples of modern genetic methods and their practical application in the field of extended-spectrum β-lactamase detection. Since extended-spectrum β-lactamases are the main mechanism of Gram-negative bacterial resistance to oxyimino-cephalosporins, rapid and accurate detection is requested in common clinical practice.Conclusions: Currently, the detection of extended-spectrum β-lactamases is primarily based on the determination of bacterial phenotypes rather than genotypes. This is because therapeutic decisions are based on assessing the susceptibility rather than presence of resistance genes. One of the main disadvantages of genetic methods is high costs, including those of laboratory equipment. On the other hand, if these modern methods are introduced into diagnostics, they often help in rapid and accurate detection of certain microorganisms or their resistance and pathogenic determinants.
Keywords: Genetic detection/Antibiotic resistanc/β-lactamase/Review